A 59‐Year‐Old Man With “Racial Characteristics” - Wright, Jackson T. (J Clin Hypertens (Greenwich), 2007)
This case discussion was presented originally in an open forum on May 5, 2006, in Baltimore, MD, sponsored by the Department of Veterans Affairs Maryland Health Care System and the University of Maryland School of Medicine as part of an ongoing series of historical clinicopathological conferences.